First Report of Agroathelia rolfsii Causing Southern Blight on Lippia ( Phyla canescens ) in Guangzhou, China - You, Yi; Zou, Chunping; Zhu, Genfa; Yang, Fengxi; Cai, Xixi; Li, Jianying; Qin, Hongjie; Wu, Haoping (Plant disease, 2024)
Lippia (Phyla canescens) is a fast-growing, mat-forming, and prostrate perennial plant well adapted to infertile, high-saline, and drought environments (Leigh, et al. 2004). It arrived in China from Japan as a flowering ground cover in 2001 (Cai, et al. 2004). In June 2022, southern blight appeared in our nursery of the Floriculture Research Institute of Guangdong Academy of Agricultural Sciences. High temperature and damp environment are major factors for this disease. The symptoms of top-layer plants were not easily detected, but they were slightly yellowed. A yellowish-brown water-soak lesion appeared on the stems and lowest leaves exposed to soil. White mycelium appeared in the middle stage. Finally, the surface plants showed water-soak decay, and a mass of beige to black-brown rapeseed-shaped sclerotia appeared on the residue and surrounding soil; these plants died. Sclerotia and mycelia were collected from disease tissue, and after surface sterilization, sclerotia was cultured on potato dextrose agar (PDA) at 28±2°C in an incubator without light. Eight fungal isolates with similar colony morphologies were consistently isolated by purifying from different sampling areas. The isolates exhibited obvious septa and a clamp connection structure within the white mycelium. The average growth rate was 26.86±0.06 mm/day. Numerous white granular sclerotia were produced on the mycelium 6 days later. The sclerotia with a diameter of 1.24±0.07mm (n=189) gradually changed from diage to yellow to brown. A typical strain B1 was selected for further identification, targeting its 18S rRNA and LSU rRNA sequences (Yang, et al. 2011; Xue, et al. 2019). Its 18S rRNA sequence (GenBank Accession No. OR517233, 1626 bp) is 99.63% and 99.57% identical to Athelia rolfsii (AY665774, 1179bp; KC670714, 1775bp; JF819726, 1781bp). Its LSU rRNA sequence (OR539570, 757 bp) is 99.87% identical to Agroathelia rolfsii (OR526537, 904 bp). For Athelia rolfsii, a synonym of Agroathelia rolfsii, by combining the morphological characteristics and molecular identification, the isolate pathogen B1 was confirmed to be Agroathelia rolfsii (the teleomorph of Sclerotium rolfsii). To fullfill Koch's postulates, we inoculated the mycelial plugs to healthy lippia stems and leaves which has grown for one year, with PDA plugs free of mycelium as the control. All the plants were kept in a greenhouse at 28±2°C with a 14-h photoperiod and 80% relative humidity. Each treatment was repeated thrice and vaccinated with 6 points. At 7 d following inoculation, all plants inoculated with B1 showed typical symptoms, but the control group was asymptomatic, and sclerotia appeared 17d after inoculation. Using the same protocol mentioned above, pathogenic fungal was reisolated only from treated groups, but not from the control group. Chose three of the pathogens for 18S rRNA and LSU rRNA sequencing, the results showed 100% identity to B1, the same as its microstructure. There are few reports about the disease on P. canescens. Sosa (2007) investigated the pathogens on P. canescens in Argentina, 16 fungi were found but no A. rolfsii. Sclerotium rolfsii were identified on P. nodiflora or P. lanceolata (Michaux) Greene in America (Farr, et al. 1989). To our knowledge, this is the first report in China. Because this pathogen has wide-ranging hosts and causes serious damage, the results from this study will offer guidance for the prevention and treatment of this disease.